2011
DOI: 10.1021/jf201796x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Interaction between Ilaprazole and Bovine Serum Albumin without or with Different C-Ring Flavonoids from the Viewpoint of Food–Drug Interference

Abstract: The interaction between ilaprazole and bovine serum albumin (BSA) has been investigated in the absence and presence of four popular flavonoids with different C-ring structures, quercetin, luteolin, taxifolin, and (+)-catechin, by means of fluorescence spectroscopy. The results indicated that ilaprazole had a strong ability to quench the intrinsic fluorescence of BSA, and site marker competitive experiments indicated that the binding of ilaprazole to BSA primarily took place in subdomain IIA. The quenching proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…It has been reported that the polyphenols of average human dietary intake is about 1 g/day, with two-third being flavonoids (Scalbert and Williamson, 2000). Up to now, there are only few studies on the influence of flavonoids on drugs-plasma proteins interaction (Mohseni-Shahri et al, 2014;Shi et al, 2012;Zhang et al, 2011). To our knowledge, the influence of flavonoids on NDP binding plasma proteins has still not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the polyphenols of average human dietary intake is about 1 g/day, with two-third being flavonoids (Scalbert and Williamson, 2000). Up to now, there are only few studies on the influence of flavonoids on drugs-plasma proteins interaction (Mohseni-Shahri et al, 2014;Shi et al, 2012;Zhang et al, 2011). To our knowledge, the influence of flavonoids on NDP binding plasma proteins has still not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption, distribution, metabolism and excretion properties, as the stability and toxicity of antioxidants, can be significantly affected by binding to serum albumin. First, the antioxidant-serum albumin interaction plays a dominant role in the bioavailability of antioxidants because the bound fraction of antioxidants is a depot, whereas the free fraction of antioxidants is active (Zhang et al, 2011). Second, if an antioxidant is metabolized and excreted from the body too fast because of low protein binding, the antioxidant cannot exert any benefit.…”
Section: Introductionmentioning
confidence: 99%
“…BSA contains two tryptophan residues, Trp212 (located within a hydrophobic pocket of the protein) and Trp134 (located on the surface of the protein molecule), which show intrinsic fluorescence (22). Fluorescence spectroscopy is an appropriate method to determine the interaction between small molecules and bioma cromolecules (23)(24)(25). In this work, we systematically evaluated the binding affinities of BSA with three oleanane-type triterpenoids, i.e.…”
Section: Introductionmentioning
confidence: 99%